HUKUM JENEWA DAN SERANGAN CAST LEAD OLEH ISRAEL KE PALESTINA - Age Sulistyoningsih; Tiffany Setyo Pratiwi (Dauliyah Journal of Islamic and International Affairs, 2019)
An armed conflict between Israel and Palestine has been going since the Balfour Declaration and Resolution Number 181 of 1947 from Britain and the United Nations for the establishment of an Israeli state on Palestinian land. One attack called the Cast Lead operation by Israel against Palestine during December 27, 2008 to January 19, 2009 which killed many civilian casualties was a violation of Israel on the principle of proportionality in international humanitarian law. The principle stipulates that before the decision to make an attack is taken, consideration should be given to the military impact that might be experienced by civil society. This paper attempts to analyze Cast Lead operations from the principle of proportionality in Geneva Protocol I paragraph 51, 51 (5) and 48. This paper finds that Cast Lead attacks are a violation of the principle of proportionality in terms of time, focus, and attack technology. This study uses an explanative qualitative methodology and based on secondary data from books, journals, articles, magazines, laws document, and the internet.